Global Financial Stability Report, June 2002 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report, 2002)
This June 2002 issue of the Global Financial Stability Report analyzes developments and issues in world markets. The report highlights that the economic recovery that began during the first quarter of 2002 has brought improvements in financial market conditions. Mature equity and bond markets have further stabilized. Most emerging market countries continue to have access to international capital markets, and their bond spreads have declined. The near-term outlook thus appears largely free of imminent threats to the global financial stability.